ASYNCHRONOUS PARALLEL COMPUTING OF STRUCTURAL NON-STATIONARY RANDOM SEISMIC RESPONSES - LIN, JIAHAO; WANG, XICHENG; WILLIAMS, F. W. (International journal for numerical methods in engineering, 1997)
An asynchronous parallel algorithm is developed in this paper. It is based on the newly developed sequential pseudo‐excitation method for structural non‐stationary random responses, used with the high precision direct (HPD‐S) integration method. Examples run on a Transtech Paramid MIMD parallel computer show that it has good accuracy and gives very high speed‐up and efficiency. © 1997 John Wiley & Sons, Ltd.